Penguatan Nilai-nilai Moderasi Beragama Melalui Program Pengajaran Agama di Desa Tewang Kadamba - Prasinartha Prasinartha; Rahmadi Nirwanto; Raisa Vienlentia; Mario Tahulending; Anggi Resti; Andre Pratama; Abi Umaroh; Cut Jordi; Esterika Wulandari; Fazry Rasyid1; Nadrah Afifah; Riska Furi; Rika Rika; Taqiyya Kamila (Lembaga Pengembangan Kinerja Dosen, 2024)
This study discusses the application of religious moderation in an effort to build a peaceful and tolerant community in Tewang Kadamba Village, Central Kalimantan. This village is known for its cultural and religious diversity, where the Dayak Kaharingan tribe is the majority of the population while Hinduism, Islam, and Christianity live side by side harmoniously. However, there are challenges related to the lack of motivation in worship activities and the shortage of Islamic religious teachers in the village. This is a serious concern because it can affect the social and religious life of the community. The Tewang Kadamba Village KKN Team took the initiative to empower the community through strengthening religious values ​​by involving the younger generation and cadres in the religious teaching program. This program is expected to encourage positive changes in religious life and social life in the village. This study uses the Participatory Action Research (PAR) method and literature study, with the aim of evaluating the effectiveness of the religious teaching program in improving the understanding and practice of religious moderation values ​​among the Tewang Kadamba Village community. It is hoped that the results of the study can provide useful suggestions for the development of religious teaching programs in Tewang Kadamba Village, so that they can support the formation of a religious, tolerant, and peaceful society